SISTEM MONITORING SERVICE KENDARAAN BERKALA DI ASTRIDO TOYOTA PONDOK INDAH DENGAN METODE AHP: Bahasa Indonesia - Romadhon, Fajar Gais; Trista, Riezca Talita (Yayasan Bina Internusa Mabarindo, 2023)
The aim of this research is to develop an effective and efficient periodic vehicle service monitoring system. The research methodology used in the data processing system is the literature study method, which involves collecting data from various library sources, journals, and other books that serve as a basis for analyzing the issues discussed in the research. Additionally, the field study method is employed, including direct observation through interviews and observations. The Analytical Hierarchy Process (AHP) is used as the algorithm to solve the problem. The result of this research is the development of an application tool programmed in Java and data storage using a MySQL database, enabling effective, efficient, and practical decision-making in the monitoring process at Astrido Toyota Pondok Indah.